Enterprise Web 2.0 fundamentals - Sankar, Krishna (Cisco Press, 2009)
An introduction to next-generation web technologies This is a comprehensive, candid introduction to Web 2.0 for every executive, strategist, technical professional, and marketer who needs to understand its implications. The authors illuminate the technologies that make Web 2.0 concepts accessible and systematically identify the business and technical best practices needed to make the most of it. You'll gain a clear understanding of what's really new about Web 2.0 and what isn't. Most important, you'll learn how Web 2.0 can help you enhance collaboration, decision-making, productivity, innovation, and your key enterprise initiatives. The authors cut through the hype that surrounds Web 2.0 and help you identify the specific innovations most likely to deliver value in your organization. Along the way, they help you assess, plan for, and profit from user-generated content, Rich Internet Applications (RIA), social networking, semantic web, content aggregation, cloud computing, the Mobile Web, and much more. This is the only book on Web 2.0 that: Covers Web 2.0 from the perspective of every participant and stakeholder, from consumers to product managers to technical professionals Provides a view of both the underlying technologies and the potential applications to bring you up to speed and spark creative ideas about how to apply Web 2.0 Introduces Web 2.0 business applications that work, as demonstrated by actual Cisco® case studies Offers detailed, expert insights into the technical infrastructure and development practices raised by Web 2.0 Previews tomorrow's emerging innovations-including "Web 3.0," the Semantic Web Provides up-to-date references, links, and pointers for exploring Web 2.0 first-hand Krishna Sankar, Distinguished Engineer in the Software Group at Cisco, currently focuses on highly scalable Web architectures and frameworks, social and knowledge graphs, collaborative social networks, and intelligent inferences. Susan A. Bouchard is a senior manager with US-Canada Sales Planning and Operations at Cisco. She focuses on Web 2.0 technology as part of the US-Canada collaboration initiative. Understand Web 2.0's foundational concepts and component technologies Discover today's best business and technical practices for profiting from Web 2.0 and Rich Internet Applications (RIA) Leverage cloud computing, social networking, and user-generated content Understand the infrastructure scalability and development practices that must be address-ed ...